Asistensi Pelaporan Pajak oleh Relawan Pajak Universitas Methodist Indonesia - Goh, Thomas Sumarsan; Purba, Dimita H. P.; Rumapea, Melanthon; Sembiring, Rasmulia; Simanjuntak, Arthur; Ginting, Mitha Christina; Jamaluddin, Jamaluddin; Elisabeth, Duma Megaria; Sagala, Farida; Sagala, Lamria (Jurnal Pengabdian Pada Masyarakat METHABDI, 2024)
The campus tax volunteer value chain refers to the contributions and benefits provided by active tax volunteers to help in providing tax information and knowledge and also assist in reporting taxpayers' tax returns. Volunteers give guidance to individuals or groups who need assistance in managing their taxes, such as filling out tax returns or understanding tax rights and obligations. Regional Office of DJP Sumbagut I will give awards and recognition to tax volunteers who have contributed significantly to increasing tax awareness in the community.